Considering the Jurisprudential and Legal Examination of the Concept of Right and Property - Seyyed Alireza Froughi (آموزه‌‌های فقه مدني, 2012)
In this paper, it has been emphasized on this opinion that the “right” like “property” is a conventional ordinance and each of these two concepts as independent rational validity have separate situations. Thus, the similarities of these two ordinances should not make us define one of them following the other. However, here there are two further ideas in jurisprudence and modern law that both of them in our opinion are extremes. The first view is the view of some Shiite jurists that have defined the right under the property and regarded it as a kind of property and its weaker grade. This inference has been taken while the “right” is not less than the concept of “property” in regarding to its conceptual inclusion. In contrast, in some cases in the new law, it has been interpreted as ownership right and brought under the concept of right. Muslim jurists, including Arabians and Persians, have interpreted ownership as the right of ownership under the influence of the west literature. In our opinion, this view is not correct, too; because when we recognized the “right” as a rational validity and independent conventional order other than property, neither of them placed under the other.